2019
DOI: 10.1002/slct.201903404
|View full text |Cite
|
Sign up to set email alerts
|

Generation of the Icetexane Core by Use of a Heck Strategy: Total Synthesis of Taxamairin B

Abstract: An efficient approach towards the total synthesis of Taxamairin B has been accomplished within 6 steps starting from o‐bromobenzylbromide 7 with 45% overall yield. Intramolecular Heck reaction works efficiently to furnish the 6–7‐6 fused icetexane scaffold under hydrative condition, which on restructuring affords the key β,γ‐enedione intermediate. The β,γ‐double bond has been introduced by the acid catalyzed water assisted elimination of a β‐tertiary alcohol. Later, the β,γ‐enedione on introduction of requisit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 63 publications
(20 reference statements)
0
3
0
Order By: Relevance
“…In 2019, Oh and coworkers reported a Heck reaction‐based strategy for the synthesis of taxamairin B ( 45 , Scheme 29). [106] The cyclohexanone 203 was converted to the corresponding lithium enolate upon treatment with lithium N , N ‐diisopropylamide (LDA), which underwent smooth alkylation with the o‐ bromobenzyl bromide 204 to furnish the benzylated cyclohexanone 205 . A 1,2‐addition of an allyl group under Barbier conditions generated a mixture of diastereoisomeric tertiary alcohols 206 , the configuration of which is inconsequential [107] .…”
Section: Highlighted Recent Synthetic Efforts Toward Icetexanesmentioning
confidence: 99%
“…In 2019, Oh and coworkers reported a Heck reaction‐based strategy for the synthesis of taxamairin B ( 45 , Scheme 29). [106] The cyclohexanone 203 was converted to the corresponding lithium enolate upon treatment with lithium N , N ‐diisopropylamide (LDA), which underwent smooth alkylation with the o‐ bromobenzyl bromide 204 to furnish the benzylated cyclohexanone 205 . A 1,2‐addition of an allyl group under Barbier conditions generated a mixture of diastereoisomeric tertiary alcohols 206 , the configuration of which is inconsequential [107] .…”
Section: Highlighted Recent Synthetic Efforts Toward Icetexanesmentioning
confidence: 99%
“…2 Bioactivity screening of 1 showed that it has potent cytotoxicity against MCF-7 cells (human breast adenocarcinoma) in vitro 3 and gives selective inhibition of prostate cancer cells. 4 However, biological activity screening and mechanistic investigations have been hampered by the scarcity of 1 in nature. Structurally, brevitaxin (1) contains an unusual 6/7/6/ 6 tetracyclic core, which includes a trans-substituted 1,4benzodioxin and a tropone ring skeleton in a highly unsaturated and oxygenated architecture (Figure 1b).…”
mentioning
confidence: 99%
“…The [6,7,6]-tricyclic core was constructed by an intramolecular hydrative Heck strategy. 18 The catalysts provide an efficient synthetic method for many natural products and useful building blocks in organic synthesis.…”
mentioning
confidence: 99%
“…Recently, we reported the total synthesis of taxamairin B (six steps from o -bromobenzyl bromide) in good yield under mild conditions. The [6,7,6]-tricyclic core was constructed by an intramolecular hydrative Heck strategy . The catalysts provide an efficient synthetic method for many natural products and useful building blocks in organic synthesis.…”
mentioning
confidence: 99%